2013
DOI: 10.4137/vrt.s12140
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models Utilized in HTLV-1 Research

Abstract: Since the isolation and discovery of human T-cell leukemia virus type 1 (HTLV-1) over 30 years ago, researchers have utilized animal models to study HTLV-1 transmission, viral persistence, virus-elicited immune responses, and HTLV-1-associated disease development (ATL, HAM/TSP). Non-human primates, rabbits, rats, and mice have all been used to help understand HTLV-1 biology and disease progression. Non-human primates offer a model system that is phylogenetically similar to humans for examining viral persistenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 144 publications
0
23
0
Order By: Relevance
“…Of the animal models of HTLV-1 infection, the rabbit model is perhaps the most amenable to experimentation, although none of the human diseases associated with HTLV-1 infection have been recapitulated therein [ 64 , 65 ]. With this system, Li et al have shown that the tax/rex mRNA levels in PBMCs peak one week after inoculation of rabbits with γ-irradiated HTLV-1-produing cells [ 66 ].…”
Section: Htlv-1 Infection and Its Outcomesmentioning
confidence: 99%
“…Of the animal models of HTLV-1 infection, the rabbit model is perhaps the most amenable to experimentation, although none of the human diseases associated with HTLV-1 infection have been recapitulated therein [ 64 , 65 ]. With this system, Li et al have shown that the tax/rex mRNA levels in PBMCs peak one week after inoculation of rabbits with γ-irradiated HTLV-1-produing cells [ 66 ].…”
Section: Htlv-1 Infection and Its Outcomesmentioning
confidence: 99%
“…Previously, rabbits and transgenic mice were used to productively study viral persistence/immune responses and importance/function of viral genes, respectively [83]. However, none of these animal models has offered the ability to study HTLV-1 viral infection and leukemia/lymphoma development.…”
Section: ‘Humanized’ Mouse Modelmentioning
confidence: 99%
“…Mouse models have traditionally been cost-effective and easy to develop and maintain: however, HTLV-1 transmission in mice using usual methods of infection does not produce reliable infection and virus expression due to the inefficient fusion of HTLV-1 envelope with murine cells (Hajj et al 2012; Lairmore et al 2005). Hence, mice have been manipulated to establish HTLV-1 infection through the generation of transgenic and humanized mice models (Dodon 2014; Panfil et al 2013). The first humanized mouse model was generated by introducing the SCID mutation that impaired the development of mature B and T cells thus improving engraftment efficiency.…”
Section: Introductionmentioning
confidence: 99%